Impact Assessment of Orography on the Extreme Precipitation Event of July 2010 over Pakistan: A Numerical Study - Khan Muhammad Tahir; Yan Yin; Yong Wang; Zaheer A. Babar; Dong Yan (Advances in Meteorology)
The topography influences monsoon precipitation and gives rise to significant rainfall events in South Asia. The physical mechanism involved in such events includes mechanical uplifting, thermodynamics, small scale cloud processes, and large scale atmospheric circulations. The investigation into orographic precipitation is pursued by synoptic and model analysis. Deep convection occurs as warm moist airflow is channeling over steep mountains. WRF model coupled with Morrison double moment scheme is used to assess the relative impact of topography on extreme rainfall event of 26–30 July 2010 in Pakistan. Two sensitivity tests with full topography (CTL) and reduced topography by 50% (LOW) are carried out. Two distinct precipitation zones over Hindukush and Himalaya mountains are identified. The topographic changes significantly affect moisture divergence and spatial and temporal distribution of precipitation. A low level jet is created on windward side of big mountains, yielding enhanced moisture flux and instability. Eddy kinetic energy significantly changes with orographic height. Energy flux created further unstabilized atmosphere and deep convection, producing wide spread heavy rainfall in the area in Himalaya foothills. Under the set synoptic conditions, orographic orientation enhanced the moisture accumulation and deep convection, resulting in occurrence of this extreme event.